2020
DOI: 10.3390/ijms21041348
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Regulation of RNA Silencing and the IFN Response as an Antiviral Defense System in Mammalian Cells

Abstract: RNA silencing is a posttranscriptional gene silencing mechanism directed by endogenous small non-coding RNAs called microRNAs (miRNAs). By contrast, the type-I interferon (IFN) response is an innate immune response induced by exogenous RNAs, such as viral RNAs. Endogenous and exogenous RNAs have typical structural features and are recognized accurately by specific RNA-binding proteins in each pathway. In mammalian cells, both RNA silencing and the IFN response are induced by double-stranded RNAs (dsRNAs) in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 111 publications
0
12
0
Order By: Relevance
“…These observations could be due to the fact that several mammalian viruses potentially encode VSR proteins, thereby masking the effect of RNAi [ 22 , 28 , 29 , 52 , 57 ]. Another putative but non-exclusive explanation could be that there is a mutual regulation of type I IFN and RNAi pathways [ 58 , 59 ]. Thus, it has already been shown that PACT can regulate MDA5 and RIG-I during virus infection and therefore the induction of type I IFN response [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations could be due to the fact that several mammalian viruses potentially encode VSR proteins, thereby masking the effect of RNAi [ 22 , 28 , 29 , 52 , 57 ]. Another putative but non-exclusive explanation could be that there is a mutual regulation of type I IFN and RNAi pathways [ 58 , 59 ]. Thus, it has already been shown that PACT can regulate MDA5 and RIG-I during virus infection and therefore the induction of type I IFN response [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…mutual regulation of type I IFN and RNAi pathways [58,59]. Thus, it has already been shown that PACT can regulate MDA5 and RIG-I during virus infection and therefore the induction of type I IFN response [60,61].…”
Section: Plos Pathogensmentioning
confidence: 99%
“…These observations could be due to the fact that several mammalian viruses potentially encode VSR proteins, thereby masking the effect of RNAi (Li et al, 2013(Li et al, , 2016Maillard et al, 2013;Qiu et al, 2017Qiu et al, , 2020. Another putative but non-exclusive explanation could be that there is a mutual regulation of type I IFN and RNAi pathways (Berkhout, 2018;Takahashi and Ui-Tei, 2020). Thus, it has already been shown that PACT can regulate MDA5 and RIG-I during virus infection and therefore the induction of type I IFN response (Kok et al, 2011;Lui et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Transfection of murine ESCs with EMCV produced intracellular EMCV-derived siRNAs with a certain size and 3’ overhangs nucleotides [ 66 , 95 ]. It seems that the simultaneous degradation of RNAi and the promotion of IFN-related responses could overlap once anti-viral immunity is initiated [ 154 , 155 ]. The suppression of MAVS in mouse embryonic fibroblasts aborted the functionality and collaboration of dsRNA sensors with IFN products [ 96 ].…”
Section: Antiviral Mechanisms Of Stem Cellsmentioning
confidence: 99%